Seismic Fragility Curves of Industrial Buildings by Using Nonlinear Analysis - Mohamed Nazri, Fadzli; Tahar, Syamimi; Saruddin, Siti Nur Aqilah; Shahidan, Shahiron (EDP Sciences, 2017)
This study presents the steel fragility curves and performance curves of industrial buildings of different geometries. The fragility curves were obtained for different building geometries, and the performance curves were developed based on lateral load, which is affected by the geometry of the building. Three records of far-field ground motion were used for incremental dynamic analysis (IDA), and the design lateral loads for pushover analysis (POA). All designs were based on British Standard (BS 5950); however, Eurocode 8 was preferred for seismic consideration in the analysis because BS 5950 does not specify any seismic provision. The five levels of performance stated by FEMA-273, namely, operational phase, immediate occupancy, damage control, life safety, and collapse prevention (CP) were used as main guidelines for evaluating structural performance. For POA, Model 2 had highest base shear, followed by Model 1 and Model 3, even though Model 2 has a smaller structure compared with Model 3. Meanwhile, the fragility curves showed that the probability of reaching or exceeding the CP level of Model 2 is the highest, followed by that of Models 1 and 3.